(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Remote Data Integrity Checking (RDIC) is a crucial technique that allows us to verify the integrity of data stored in the cloud. Over the years, various RDIC protocols have been proposed in academic literature, but they have faced challenges related to complex key management. In our project, we introduce an innovative approach to Identity-Based RDIC, leveraging secure key generation to simplify the system’s complexity and reduce the cost of establishing and managing the public key infrastructure (PKI) in RDIC schemes. Our proposed solution revolves around three main entities: the cloud server, the user, and the third-party auditor (TPA). The TPA plays a critical role in providing evidence of data integrity, ensuring that our data remains unaltered and secure within the cloud environment. Additionally, we have implemented robust security mechanisms to safeguard against unauthorized access and data tampering. Should any unauthorized modifications occur, whether by the cloud server or an unauthorized individual, the user can retrieve their original data from a trusted backup server, thus preventing data loss or corruption. The Third-Party Auditor (TPA) takes responsibility for monitoring the integrity of the cloud data on behalf of the cloud users. This is particularly useful in scenarios where users may not have the time or resources to continuously monitor their data’s integrity, as the TPA conducts regular checks and provides auditing reports back to the cloud users. This way, users can have peace of mind knowing that their data is being regularly validated and protected. By leveraging Identity-Based RDIC and incorporating the TPA, our solution aims to address the challenges of traditional RDIC protocols and provide a more efficient and secure data integrity checking mechanism for cloud storage environments.